Endovascular Stenting for Acute Ischemic Stroke Due to Cervical Artery Dissection: Nationwide Study of Stroke Recurrence - Huanwen Chen; Mihir Khunte; Marco Colasurdo; Ajay Malhotra; Dheeraj Gandhi (Stroke: Vascular and Interventional Neurology)
Background For patients with acute ischemic stroke (AIS) due to cervical artery dissection (CAD), endovascular stenting can improve and maintain vessel patency for severely stenotic or occlusive lesions. Athough prior reports have suggested equivocal functional outcomes with stenting versus no stenting for AIS‐CAD, there are currently no data on stenting and stroke recurrence. Methods This was a retrospective cohort study of the 2016–21 Nationwide Readmissions Database in the United States. Adult patients hospitalized for AIS‐CAD were included. Patients who did and did not undergo endovascular stenting were matched using propensity scores calculated using logistic regression models accounting for demographics, stroke severity, and comorbidities. The primary end point was recurrent ischemic stroke within 180 days. Secondary end points include outcomes of the index AIS‐CAD hospitalization such as routine discharge to home without rehabilitation needs, death, and intracranial hemorrhage. Results A total of 20 434 patients were included; 2368 (11.6%) underwent endovascular stenting. After propensity score matching, 2215 patients remained in the no stenting group, and 2244 remained in the stenting group. The stenting group had a significantly lower stroke recurrence risk than the no‐stenting group within 180 days (hazard ratio 0.50 [95% CI: 0.27–0.95], P = 0.034). Among patients with at least 180 days of follow‐up, the rate of recurrent stroke was 1.2% in the stenting group, which was significantly lower than 3.5% in the no‐stenting group (P = 0.017). During the index AIS‐CAD hospitalization, stenting was not associated with a different rate of routine discharge (43.8% versus 44.8%, P = 0.65) or death (8.7% versus 7.3%, P = 0.34); however, it was associated with a higher rate of intracranial hemorrhage (21.9% versus 19.0%, P = 0.027). Conclusion For patients with AIS‐CAD, endovascular stenting was associated with a lower rate of stroke recurrence. Although stenting was associated with a higher rate of intracranial hemorrhage, this phenomenon did not culminate in different rates of short‐term morbidity or mortality.